The Empirical Revolution in Economics - Salazar-Trujillo, Boris; Otero-Robles, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article proposes an explanation to the empirical revolution in economics. It argues that the search for natural and quasi-natural experiments, wherever they were available, looking for more credible identification methods, led to the creation and application of new econometric tools and to their further propagation to an increasing number of fields in Economics. The application of the new tools and research designs to the evaluation of policy interventions all over the world activated a powerful feedback systems, working from interventions to their evaluations, by means of new econometric tools, to the publication of academic articles and back to the generation of new interventions. By using networks of cocitation and semantic networks of the articles that introduced the new tools, we found traces of their impact over the practice of economists, and over the emergence of three groupings of researchers as an effect of the arrival of synthetic control in 2003.